The role of cognitive flexibility on stress in hospital medical personnel in Malang - Amallia Salzabilla Taufani; Nandy Agustin Syakarofath; Latipun Latipun; Dian Caesaria Widyasari (Fakultas Psikologi, 2022)
Covid-19 was causing a drastically changing situation, especially for healthcare workers facing increasing workloads and sudden changes in circumstances. These circumstances force health workers to adapt to these stressful changes. Cognitive flexibility is one of the protective factors for health workers to be capable of processing and coping with stress. This study aims to perceive the contribution of cognitive flexibility to stress to healthcare workers. The research hypothesis is that there is a negative role between cognitive flexibility and stress, which means the higher cognitive flexibility a health worker has, the lower the stress level. This study uses quantitative methods. Using random sampling techniques, data retrieval uses the Cognitive Flexibility Scale (CFS) and Depression Anxiety Stress Scale (DASS-21) questionnaires. The subjects of this study were 55 health workers working at hospitals in Malang, with the professional criteria of doctors, nurses, pharmacists, and midwives. Data analysis uses a simple linear regression test. The results of this study show that cognitive flexibility has a 33.3% effect on reducing stress levels in healthcare workers. Keywords: cognitive flexibility, covid-19, healthcare workers, mental health, stress